Has Generalized System of Preferences Scheme Influenced Nepalese Exports to the United States? An Empirical Analysis - Bhandari, Ganga Ram (Economic Journal of Development Issues, 2016)
This paper attempts to evaluate the impact of generalized System of Preferences (GSP) scheme on exports of Nepal to the United States (US). Nepal-US trade is very crucial because the US is still the second largest export destination of Nepal. Thus, it is pertinent to study exports of Nepal to the US under GSP scheme. Empirical results show that impact of GSP scheme is very minimal and negative. Other factors than liberal policy viz. GSP determines exports of Nepal to the US. Weakening exports capacity and declining trade transaction of Nepal to the US is of major concern. In this regard, to sustain the export of existing but declining exportable items like garment, carpet, pashmina and handicrafts and development and promotion of GSP eligible new products and services will only be the resolution of this obstruction.Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 29-39